Implementasi Pembelajaran Kolaboratif dalam Mengembangkan Keterampilan Sosial Dan Emosional Peserta Didik Fase B melalui Pembelajaran Berbasis Masalah - Pertiwi, Alif Lifia Ade; Sumarno, S.; Munawar, Herfi Atrinawati (Education Journal : Journal Educational Research and Development, 2024)
This study aimed to assess the impact of implementing collaborative learning, namely through problem-based learning, on the development of social and emotional skills in phase B pupils. This refers to a specific sort of quantitative experimental research that utilises a pretest posttest design. The sampling method employed in this study was a saturated sample of 28 kids in the fourth grade, comprising 11 male and 17 female pupils. The mean pretest score for students' social and emotional skills was 71.21, while the mean posttest score was 84.93. Research hypothesis: Indeed, the integration of collaborative learning with problem-based learning has a significant impact on the development of students' social emotional skills. The null hypothesis states that there is no impact of collaborative learning combined with problem-based learning on the social emotional skills of students. The study using the paired sample t-test yielded a significance value of 0.000. The obtained significance value was below 0.05 (0.000 < 0.05), indicating acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho). The social and emotional abilities of fourth-grade students in phase B are specifically impacted by the integration of collaborative learning and problem-based learning. Specifically, the social emotional abilities of phase b students in grade IV are impacted by the combination of collaborative learning and problem-based learning. The examination of the pretest and posttest data yielded an average NGain Score of 0.7059, which falls within the high range according to the NGain Score division criteria. The average NGain percent value found was 0.70.58, showing a significant level of effectiveness. The introduction of collaborative learning through problem-based learning has a high and effective impact on students' social emotional skills.